Rainwater Harvesting as Alternative Source for Wudlu Water in Indonesia - Susilo, Gatot Eko (Civil and Environmental Science Journal (CIVENSE), 2018)
Indonesia is the country with the largest Muslim population in the world. And as a country with Muslim big population clean water for wudlu or purification must be available. Rainwater holds potential as an alternative source of wudlu water. Rainwater harvesting (RWH) for religious water supply is still very rare studied. Based on this, the research in this paper aims to calculate the potential supporting capacity of rainwater as an alternative sourceof wudlu water. Supporting capacity of rainwater harvesting (SCRWH) in this study was calculated by simulating inflow and outflow behavior at a rainwater harvesting facility in a mosque. Case study takes place at Nurul Iman Mosque in Southern Lampung. The mosque has an area of 168 m and able to accommodate 300 worshipers. Research show that the most effective reservoir size in the RWH facility in the observed mosque is between 15 to 30 m2 with SCRWH for wet years between 65% and 70% and for dry years between 44% and 53%, respectively. The availability of wudlu water in a mosque basically cannot be expected 100% comes from rain water only. In the application of RWH in a mosque the maintenance of theRWH facility must be undertaken well.